Grades 7–12 teachers' perception of computational thinking for mathematics and technology - Humble, Niklas; Mozelius, Peter (Frontiers in Education, 2023)
An ongoing trend on a global scale is the integration of computer science and programming in K-12 education. The integration has been motivated by the needs of the present and the future labour market, but also by the assumption that skills related to computer science and programming are valuable for citizens to navigate an increasingly digitalised society. Computational thinking (CT) is a concept that aims to define and summarise skills associated with programming and computer science and has received wide recognition within research and education. But how do the teachers perceive this concept, and how do they relate it to their own teaching and learning activities? This study aims to investigate and discuss teachers’ perceptions of CT in grade 7-12 mathematics and technology. Data have been collected from essay assignments in 3 instances of a professional development course on fundamental programming for grade 7-12 teachers in mathematics and technology. In the essays, the teachers reflect on CT in relation to their subjects mathematics and technology and their teaching and learning activities in these subjects. With a theoretical framework for CT, the collected data have been analysed with a directed content analysis approach to identify categories of interests for CT in relation to grade 7-12 mathematics and technology. Results of the study show that the teachers perceive both opportunities and challenges in applying the CT concept in their teaching and learning activities. For example, that it can strengthen the subjects through new practices and reinforce old practices; but also, that it could be too complex and perceived as difficult by some students. Further, many of the teachers perceive CT not only to be relevant for mathematics and technology, but also for learning in general. The findings of this study can be used by teachers and other stakeholders in the design of classroom activities that apply the CT concept.